2013
DOI: 10.1177/2049463713502005
|View full text |Cite
|
Sign up to set email alerts
|

Venom: the sharp end of pain therapeutics

Abstract: Adequate pain control is still a significant challenge and largely unmet medical need in the 21st century. With many small molecules failing to reach required levels of potency and selectivity, drug discovery is once again turning to nature to replenish pain therapeutic pipelines. Venomous animals are frequently stereotyped as inflictors of pain and distress and have historically been vilified by mankind. Yet, ironically, the very venoms that cause pain when directly injected by the host animal may actually tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…TRPV1 | DkTx | transgenic C. elegans | pore turret | capsaicin S ensory neurons of the pain pathway (i.e., nociceptors) are excited by a multitude of plant and animal toxins that inflict pain (1). However, while some of these toxins produce this effect indirectly by causing tissue damage and the release of algogenic substances from nonneuronal cells, others directly elicit pain mainly by targeting membrane proteins selectively expressed by nociceptors (1)(2)(3)(4)(5). One of these membrane proteins, the transient receptor potential vanilloid 1 (TRPV1), is a nonselective cation channel activated by several plant and animal toxins, noxious heat, protons, and bioactive lipids such as anandamide and 15-HPETE (6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…TRPV1 | DkTx | transgenic C. elegans | pore turret | capsaicin S ensory neurons of the pain pathway (i.e., nociceptors) are excited by a multitude of plant and animal toxins that inflict pain (1). However, while some of these toxins produce this effect indirectly by causing tissue damage and the release of algogenic substances from nonneuronal cells, others directly elicit pain mainly by targeting membrane proteins selectively expressed by nociceptors (1)(2)(3)(4)(5). One of these membrane proteins, the transient receptor potential vanilloid 1 (TRPV1), is a nonselective cation channel activated by several plant and animal toxins, noxious heat, protons, and bioactive lipids such as anandamide and 15-HPETE (6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Notably, disruption of membrane integrity appears to be the most common mechanism of action for known, venom-derived antimicrobial peptides and enzymes (Stocker and Traynor 1986;Perumal Samy et al 2017) of long-standing (Glaser 1948) and significant biotherapeutic interest, including MDR (Xie et al 2003) and nociception (Trim and Trim 2013). It is unclear at present 15 to which extent this form of parallel convergent evolution extends beyond Enterococcus or other antimicrobial resistance mechanisms, such as antibiotic resistance genes against last resort antibiotics found on mobile genetic elements McGann et al 2016) found in multiple continents.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the oral microbiome of the non-venomous Burmese python (Python bivittatus) has also been reported to be native and not derived from prey guts (Costello et al 2010). 5 As venom glands are connected to the tip of envenomation apparatus via a persistently open duct which is continuously exposed to the environment (Trim and Trim 2013), envenomation apparatus could be compared to clinical catheterisation assemblies: a transcutaneous needle resting on a non-sterile environment, connected to a continually open duct, leading to a liquid vessel. Such devices develop biofilms within a few days, making weekly catheter replacement 10 necessary (Loveday et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…With clinically used analgesic drugs including NSAIDs and opioid antagonists failing to reach the required levels of potency and selectivity, drug discovery is once again turning to nature to replenish pain therapeutic pipelines, with animal venoms proven to have potential as new types of analgesic medicine . In this study, we described the purification of an analgesic peptide (SsmTX‐I) from the crude venom of the centipede S. subspinipes mutilans , which has been used as traditional analgesic medicine in China for hundreds of years.…”
Section: Discussionmentioning
confidence: 99%